2023
DOI: 10.1161/atvbaha.122.317715
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Arterial Stiffness and New-Onset Heart Failure: The Kailuan Study

Abstract: BACKGROUND: Arterial stiffness (AS) was associated with heart failure (HF) in previous studies based on specific populations with small samples and the effects of age and blood pressure on AS were not taken into account. Whether AS was independently associated with new-onset HF in community dwellers has not been fully investigated to date. METHODS: Individuals who participated in health evaluations and underwent synchronized brachial-ankle pulse wave ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…Increases in large elastic artery stiffness (i.e., increased aortic PWV and intrinsic mechanical wall stiffness) with aging is a major independent predictor of age‐associated clinical CVD (Vasan et al., 2022 ), impaired glucose tolerance (Zheng et al., 2023 ), kidney dysfunction (Ford et al., 2010 ), cognitive impairment (Thorin‐Trescases et al., 2018 ), and diabetic retinopathy (An et al., 2021 ). Fisetin supplementation reduced arterial stiffness (aortic PWV) in old wild‐type mice by reducing aortic intrinsic mechanical wall stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in large elastic artery stiffness (i.e., increased aortic PWV and intrinsic mechanical wall stiffness) with aging is a major independent predictor of age‐associated clinical CVD (Vasan et al., 2022 ), impaired glucose tolerance (Zheng et al., 2023 ), kidney dysfunction (Ford et al., 2010 ), cognitive impairment (Thorin‐Trescases et al., 2018 ), and diabetic retinopathy (An et al., 2021 ). Fisetin supplementation reduced arterial stiffness (aortic PWV) in old wild‐type mice by reducing aortic intrinsic mechanical wall stiffness.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Longitudinal cohort studies based on the general Chinese population have shown that borderline arterial stiffness (1400 ≤baPWV <1800 cm/s) is an independent risk factor for the onset of heart failure. 25 Another study showed that baPWV >1400 cm/s was significantly associated with coronary heart disease and stroke, 26 suggesting that baPWV at >1400 cm/s can reflect CVD risk at an earlier stage. Therefore, the present study defined elevated arterial stiffness as baPWV ≥1400 cm/s.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, recent data indicate that pulse wave velocity may be an important predictor of future heart failure. 141 Therefore, as for abnormally high ABI, aortic stiffness may not reflect the presence of subclinical atherosclerosis, and any association with cardiovascular events or CVD may result from other mechanisms. A variety of other tests such as retinal vessel caliber and skin autofluorescence also cannot be used to infer the presence of subclinical atherosclerosis.…”
Section: Measures Of Vascular Function or Anatomy But Do Not Indicate...mentioning
confidence: 99%